THE INFLUENCE OF SYSTEMIC FUNCTIONAL LINGUISTICS ON TEACHING FUNCTIONAL TEXTS IN A WRITING CLASS - Leni Irianti (ELTR Journal, 2019)
This article analyzed the functional text and register in Systemic-Functional theoretical framework. It explored how both register and genre realized in pedagogic models especially in English business writing course. In English as a foreign-language, writing for functional texts is considered important in teaching learning activities. The register and genre were considered in composing the application letter. It was used the teaching cycle of Genre Based Approach (henceforth GBA) to connect between register and genre in the writing functional text especially in writing application letter activities. There were the models of functional writing provided and the students followed the teaching cycle of GBA the students compose the letter of application. The most noticeable qualities of generic structures and tenor awareness tended to be emphasized by lecturer over less-evident lexico-grammatical patterns. It is also important of how the students’ recognize stages of formal letters. This was suggested that choice of genre and more systematic attention to details of register (especially tenor) awareness are truly important in writing formal letter for learners English for Business Writing class.